Anxiolytic drugs and altered hippocampal theta rhythms: The quantitative systems pharmacological approach. (March 2014) - John, Tibin; Kiss, Tamás; Lever, Colin; Érdi, Péter
<x xml:space="preserve">Abstract</x> The spirit of systems pharmacology was adopted to study the possible mechanisms of anxiolytic drugs on hippocampal electric patterns. The frequency of the hippocampal theta rhythm increases linearly with the intensity of electrical stimulation to the brainstem. The reduction of mean theta frequency in this paradigm predicts the clinical efficacy of anxiolytic drugs. The purpose of this study was to investigate the mechanisms by which anxiolytics produce their characteristic effects on the slope and intercept of the stimulus-frequency relationship of hippocampal theta. A network of neuron populations that generates septo-hippocampal theta rhythm was modeled using a compartmental modeling technique. The influence of cellular and synaptic parameters on network frequency was studied. Results show that halving the rate of rise and fall of pyramidal hyperpolarization-activated (Ih) conductance lowers nPO elicited theta frequency at low levels of stimulation. Results also suggest that increasing the decay time constant of inhibitory post-synaptic current can reduce the frequency of low nPO stimulation elicited theta rhythm, while maximal synaptic conductance of GABA-mediated synapses has little effect on frequency. Given their similar effect on network dynamics as by known anxiolytics, these parameter manipulations may mimic or predict the biophysical manifestations of anxiolytic action within the septo-hippocampal system.